Pengujian Kapasitas Lentur dan Kapasitas Tumpu Konstruksi Dinding Alternatif Berbahan Dasar Epoxy Polystyrene (EPS) - Setiawan, Agus (Bina Nusantara University, 2010)
This research has an objective to investigate the capacity of alternative wall panel construction, with EPS (Epoxy Polystyrene) as a based material. EPS with 5 cm of thickness and 1 m of width used as specimens at this research. The specimens reinforced with wire mesh (?4 ? 150 mm) both sides, and finished by mortar cement with 1,5 and 3 cm of thickness. Each specimen was tested in the laboratory to obtain their flexural capacity and bearing capacity. Specimen with 8,5 cm of thickness has 150 kg/m2 of flexural capacity, while specimen with 11 cm of thickness has 450 kg/m2 of flexural capacity. Alternative wall panel with EPS, can be used as a bearing wall, with 2,9 tons/m of bearing capacity.